A kinetic Study of the Rate Reaction of Alkaline Phosphatase in Tuberculosis - Hassan, H. G.; Ismahil, P. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Serum alkaline phosphatase activity has been investigated in three major types of tuberculosis (TB). These were Extra pulmonary primary, Acute miliary, and Primary tuberculosis. Activities were found elevated in these cases studied at basic PH and 37 C. The study concentrated an a comprehensive determination of the rate reaction kinetics of the enzyme reaction in both normal and TB sera. The pseudo first — order plot reflects both values of the first — order association constant (K I) and the half life time (t1/2) of the enzymatic reaction. The activation energy of the reaction (ES-complex formation) with Hill coefficient (n) were both estimated using Arrhenius and Hill plots respectively.